Credibility of EWOM and Consumer Satisfaction on Food/Health Supplement Products during the COVID-19 Pandemic - Dahesihsari, Rayini; Novita, Novita; Yosua, Immanuel (Rescollacom (Research Collaborations Community), 2024)
During the pandemic, many information about the function of various food and health supplement products for prevention/recovery from Covid-19 infection circulated through EWOM (electronic word of mouth), which was believed by consumers, even though not all of them were proven to be true. This study aims to examine the role of perceived EWOM credibility on consumer satisfaction with food/health supplement products during the COVID-19 pandemic. The theoretical framework guiding this research is Source Credibility Theory, which provides a lens to examine how the credibility of EWOM sources affects consumer satisfaction. The participants were 103 people aged 19-25 years who had purchased and consumed food/health supplement products during the COVID-19 pandemic and had read EWOM about information/reviews of the products they consumed. Participants filled out a questionnaire that measured their perceived EWOM credibility and consumer satisfaction. The data were analyzed using multiple linear regression. The results showed that perceived EWOM credibility positively influenced consumer satisfaction. Aspects of perceived EWOM credibility, included argument quality and homophily had a significant influence on consumer satisfaction. The quality of arguments positively contributes to enhancing customer satisfaction, whereas homophily, on the other hand, has a negative impact. Consequently, a heightened perception of EWOM credibility, particularly concerning the quality of argument presented directly correlated with increased participant satisfaction with the food/health supplement products they had consumed. The findings of this study hold practical implications for the promotion of food and health supplements, emphasizing the significance of EWOM credibility. Additionally, the results underscore the importance of fostering information literacy among consumers in this domain. For instance, strategies could include the dissemination of infographics illustrating methods to assess information quality and discern genuine information from hoaxes. On the other hand, relying solely on information based on shared backgrounds does not fully support the attainment of satisfaction in consumption.